Lean Production—An Evaluation of the Possibilities for an Employee Supportive Lean Practice. Issue 1 (4th January 2012) - Hasle, Peter
Abstract Lean is a contested concept. It has been praised for empowering employees, and it has been criticized for intensifying work and impairing the health and well‐being of employees. This article is reviewing the literature on the relations between lean and employees, and suggests ways for the development of an employee‐supportive lean practice. There is good evidence of lean's adverse consequences for low‐skilled employees in the auto industry and other assembly type manufacturing work, but there are also examples of more positive outcomes. It is important to emphasize that, not only lean thinking, but also the context and implementation of lean have consequences for employee outcomes. Research is still needed to demonstrate it in real life, but this analysis of lean thinking, context, and implementation suggests possibilities for developing a lean practice that is genuinely employee‐supportive. © 2011 Wiley Periodicals, Inc.